Restorative Therapies after Stroke: Drugs, Devices, and Robotics - Srivastava, M. V. Padma; Kuthiala, Neha (Annals of the National Academy of Medical Sciences (India), 2019)
Restorative therapies aim to improve outcome by salvaging threatened brain, as with reperfusion or neuroprotective drugs and also by promoting plasticity within surviving neural tissue. Restorative therapies typically have a therapeutic time window measured in days and weeks and so have the potential to be assessed by a large fraction of patients with a new stroke. Examples of such brain repair therapies include growth factors, cell-based therapies, and devices. Positive clinical trials have been reported in human studies for several classes of restorative therapy after stroke. These include robotics, constrain-induced movement therapy (CIMT), and pharmacological therapy, such as levodopa and selective serotonin reuptake inhibitors. In addition, several forms of noninvasive cortical stimulation, such as rapid transcranial magnetic stimulation, transcranial direct current stimulation, and theta-burst stimulation, have shown promise in early phase studies. The current review gives a glimpse of the existing strategies, those on the anvil of implementation and those with a hope of launch in near future.
Keywords: stroke; stem cell therapy; vascular endothelial growth factor; physiotherapy